(3GdQSGFd GdWHjI GdSfLQjIs - (3HTQ Hf jYbhH Hf ESMGb GdSfLQj GdeJWHH, CHj Sgds
(3ChdgG (B:s
(3HYO GdHSedI GdQSGdI GdChdi ai GdebGdI GdKGdKI ef cJGd GdQSGFd GdWHjI hgj ChLGY GdeaGUd YTQI aUhd , GdaUd GdChd CQHY GHhGH s
(3BNQgG (B:s
(3hjJabO PcGA SeYg hMGd cdGeg hYbdg aCSJYRdgG jYQa dgG GdaQGSI JeJ GdebGdI GdKGdKg s
(3eLdO jTJed Ydi GdebGdI GdKGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B91 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs